Roles of the Insular Cortex in the Modulation of Pain: Insights from Brain Lesions - Starr, Christopher J. (Society for Neuroscience, 2009)
Subjective sensory experiences are constructed by the integration of afferent sensory information with information about the uniquely personal internal cognitive state. The insular cortex is anatomically positioned to serve as one potential interface between afferent processing mechanisms and more cognitively oriented modulatory systems. However, the role of the insular cortex in such modulatory processes remains poorly understood. Two individuals with extensive lesions to the insula were examined to better understand the contribution of this brain region to the generation of subjective sensory experiences. Despite substantial differences in the extent of the damage to the insular cortex, three findings were common to both individuals. First, both subjects had substantially higher pain intensity ratings of acute experimental noxious stimuli than age-matched control subjects. Second, when pain-related activation of the primary somatosensory cortex was examined during left- and right-sided stimulation, both individuals exhibited dramatically elevated activity of the primary somatosensory cortex ipsilateral to the lesioned insula in relation to healthy control subjects. Finally, both individuals retained the ability to evaluate pain despite substantial insular damage and no evidence of detectible insular activity. Together, these results indicate that the insula may be importantly involved in tuning cortical regions to appropriately use previous cognitive information during afferent processing. Finally, these data suggest that a subjectively available experience of pain can be instantiated by brain mechanisms that do not require the insular cortex.